Pengembangan E-Modul Berdiferensiasi dengan Pendekatan Understanding by Design Materi Pecahan Kelas IV Sekolah Dasar - Anandha Noviyanti Putri; Surayanah Surayanah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
The diversity of elementary school students’ learning readiness, which is not yet fully accommodated by conventional teaching materials, has an impact on low conceptual understanding of mathematics, particularly fraction topics. This study aimed to develop a differentiated e-module using the Understanding by Design (UbD) approach that is valid, practical, and effective for improving the conceptual understanding of fourth-grade elementary school students. The method employed adapted the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. Data analysis included the Gregory validity test, calculation of practicality percentages, and effectiveness testing using a paired-sample t-test and N-gain analysis. The results showed that the developed e-module had very high validity (coefficient of 1), very high practicality according to students (95.5%) and teachers (96%), and effectively improved conceptual understanding, with the average pretest score increasing from 66.16 to 82.08, a significance value of 0.000, and an N-gain in the medium category. These findings reinforce that integrating differentiated instruction and the UbD framework into digital teaching materials can enhance the quality of students’ conceptual understanding. The study concludes that the differentiated e-module is feasible for use as an alternative adaptive teaching material, with implications for the development of mathematics instructional designs based on students’ needs in elementary schools.